2020
DOI: 10.1371/journal.pone.0229652
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in older Chinese patients with diabetes

Abstract: BackgroundAlthough older diabetes patients with unique characteristics should be cared carefully to improve their health-related quality of life (HRQOL), the association between diabetes and HRQOL remain unclear, especially in Asians. We aimed to compare the HRQOL between older Chinese patients with type 2 diabetes (T2D) and their age-gender-matched controls. MethodsOlder patients with T2D were recruited from a community hospital in Suzhou located in the east part of China while controls were selected from a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
3
18
0
1
Order By: Relevance
“…So, more people lived with disease for a long time, in particular, chronic non-communicable disease (NCD). Some study using EQ-5D also reported that QOL was lower among individuals with diabetes, gastrointestinal disease, hypertension, heart disease, and so on [29,30]. Our study showed that our respondents with three and above chronic diseases reported lower EQ-5D scores than other respondents, it similes to the Japan and Heilongjiang population results [25,26].…”
Section: Discussionsupporting
confidence: 64%
“…So, more people lived with disease for a long time, in particular, chronic non-communicable disease (NCD). Some study using EQ-5D also reported that QOL was lower among individuals with diabetes, gastrointestinal disease, hypertension, heart disease, and so on [29,30]. Our study showed that our respondents with three and above chronic diseases reported lower EQ-5D scores than other respondents, it similes to the Japan and Heilongjiang population results [25,26].…”
Section: Discussionsupporting
confidence: 64%
“…Of chronic diseases; T2DM is one of these diseases that physically, socially, and psychologically influence patients' quality of life in terms of both disease outcomes and treatment process. Literature reports a poor quality of life in T2DM individuals [3,4,13,18] and likewise, the current study yielded a low quality of life in T2DM individuals; which may be explained by the fact that DM complications damaging vital organs and nerves lead to life-threatening damages and thus, minimize patients' quality of life [13].…”
Section: Discussionsupporting
confidence: 47%
“…In Turkey; the number of people living with DM is estimated to be nearly 6.5 million and by 2045 the number of diabetic individuals will be almost 10.4 million by putting Turkey among one of the 10 countries where diabetes takes place most [2]. The prevalence of DM and diabetic complications increase morbidity and mortality and decrease quality of life [3,4]. İt is very essential to prevent complications in DM.…”
Section: Introductionmentioning
confidence: 99%
“…Depression and diabetes distress can reduce control of HbA1c, blood pressure, and cholesterol, treatment adherence, and overall health among patients with type 2 diabetes [ 45 ]. Medication adherence, disease severity, and depression were also found to be closely correlated with QoL [ 44 , 46 ]. CoC and providing patients with self-care skills and disease-related information may prevent the risk of disability and development of complications in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%